Accountability of Digital Platforms in the Brazilian Supreme Court: A Critical Discourse Analysis of Jovem Pans Narrative (Global Journal of Human-Social Science, 2025)
His article examines the discursive representation of the news outlet Jovem Pan regarding the Brazilian Supreme Federal Court s STF decision to reinterpret Article 19 of the Civil Rights Framework for the Internet which holds digital platforms accountable for third-party content The study employs Critical Discourse Analysis Fairclough 2019 in dialogue with authors such as Gramsci and Althusser to investigate how journalistic discourse shapes meanings around digital regulation Transcripts of Jovem Pan s videos disseminated across multiple platforms were analyzed focusing on lexical choices rhetorical strategies and discursive practices Findings show that the coverage is structured around a negative evaluative vocabulary private censorship institutional threat blow against freedom a systematic use of epistemic modality to dramatize potential risks selective intertextuality privileging dissenting voices and war-like metaphors framing the STF as an enemy of civil society The study concludes that Jovem Pan operates as an ideological media apparatus reinforcing a neoliberal hegemony of digital communication in which freedom of expression is mobilized as an absolute individual value while the corporate responsibility of big tech companies is rendered invisible The research highlights the need to advance counterhegemonic alternatives that integrate freedom of expression with democratic regulation of digital platforms
Keywords: critical discourse analysis; civil rights framework for the internet; jovem pan; digital platforms